Recent progress in pig-to-human kidney xenotransplantation - Tao, Pei; Zhou, Kaiyu (Frontiers in Immunology, 2025)
Even though the patient kept up his dialysis regimen as he had before xenotransplantation, this is a significant development for xenotransplantation. This benchmark for xenotransplantation has the following significant findings. Firstly, from the patient’s perspective, the patient was able to regain energy and quality of life and experience normal metabolic filtration (creatinine clearance) during the functional period, thanks to the transplant, which significantly reduced his need for dialysis. Secondly, this is a historic accomplishment for xenotransplantation because it set up a new global record for xenotransplantation survival that exceeds all prior attempts. Thirdly, it brings hope for solving the problem of worldwide organ shortage. Lastly, the FDA has authorized more extensive clinical trials that may include more than thirty patients from several transplant facilities.